Strategic Brand Management / 2nd Edition - Percy Larry; Pervan Simon; Rosenbaum-Elliot Richard (Oxford University Press, 2007)
This book offers a unique socio-cultural approach to brand management, enabling you to understand the different aspects of the subject. The Sociocultural Meaning of Brands, Understanding the Social Psychology of Brands, Emotion and Brands, The Symbolic Meaning of Brands, Cultural Meaning Systems and Brands, Brand Equity and Brand Building, Brand Equity, Building Brands Through Marketing Communication, Measuring Brand Performance and Equity, Managing Brands, Symbolic Brands, Low-Involvement Brands, Brands and Innovation and High Technology, Brand Stretching and Retrenching, Managing Corporate Reputation, Index.